Chloride penetration into concrete damaged by uniaxial tensile fatigue loading. (30th October 2016) - Fu, Chuanqing; Ye, Hailong; Jin, Xianyu; Yan, Dongming; Jin, Nanguo; Peng, Zhaoxiong
Highlights: Quantitative analysis of uniaxial tensile fatigue damage on chloride penetration. Binder type, exposure duration, condition, and degree of damage were considered. A simple expression was proposed to predict fatigue damage on chloride diffusivity. Abstract: In this work, the chloride penetration into concrete damaged by uniaxial tensile fatigue loading was characterized. Various fatigue-damaged concrete were exposed to two environmental conditions (i.e. immersion and drying-wetting cycles) for different durations. A quantitative correlation has been established to predict the effects of residual strains on the apparent chloride diffusivity of fatigue-damaged concrete. The experimental results show that the tensile fatigue damage can accelerate the chloride penetration in concrete by 1.5–3.0 times, when the magnitude of maximum tensile fatigue load is between 25% and 45% of the ultimate tensile load of the specimen. When the maximum fatigue load is greater than 30% of the ultimate tensile loads, the chloride penetration is substantially accelerated. In summary, the chloride ingress into concrete is dependent on the exposure condition, duration, type of binder, and degree of fatigue damage.